Assessment of the extracellular volume fraction for the grading of clear cell renal cell carcinoma: first results and histopathological findings - Adams, Lisa C.; Jurmeister, Philipp; Ralla, Bernhard; Bressem, Keno K.; Fahlenkam, Ute L.; Engel, Guenther; Siepmann, Stefan; Wagner, Moritz; Hamm, Bernd; Busch, Jonas; Makowski, Marcus R. (European Radiology, 2019)
Objectives: To assess the potential of T1 mapping–based extracellular volume fraction (ECV) for the identification of higher grade clear cell renal cell carcinoma (cRCC), based on histopathology as the reference standard. Methods: For this single-center, institutional review board–approved prospective study, 27 patients (17 men, median age 62 ± 12.4 years) with pathologic diagnosis of cRCC (nucleolar International Society of Urological Pathology (ISUP) grading) received abdominal MRI scans at 1.5 T using a modified Look-Locker inversion recovery (MOLLI) sequence between January 2017 and June 2018. Quantitative T1 values were measured at different time points (pre- and postcontrast agent administration) and quantification of the ECV was performed on MRI and histological sections (H&E staining). Results: Reduction in T1 value after contrast agent administration and MR-derived ECV were reliable predictors for differentiating higher from lower grade cRCC. Postcontrast T1diff values (T1diff = T1 difference between the native and nephrogenic phase) and MR-derived ECV were significantly higher for higher grade cRCC (ISUP grades 3–4) compared with lower grade cRCC (ISUP grades 1–2) (p < 0.001). A cutoff value of 700 ms could distinguish higher grade from lower grade tumors with 100% (95% CI 0.69–1.00) sensitivity and 82% (95% CI 0.57–0.96) specificity. There was a positive and strong correlation between MR-derived ECV and histological ECV (p < 0.01, r = 0.88). Interobserver agreement for quantitative longitudinal relaxation times in the T1 maps was excellent. Conclusions: T1 mapping with ECV measurement could represent a novel in vivo biomarker for the classification of cRCC regarding their nucleolar grade, providing incremental diagnostic value as a quantitative MR marker. Key Points: • Reduction in MRI T1 relaxation times after contrast agent administration and MR-derived extracellular volume fraction are useful parameters for grading of clear cell renal cell carcinoma (cRCC). • T1 differences between the native and the nephrogenic phase are higher for higher grade cRCC compared with lower grade cRCC and MRI-derived extracellular volume fraction (ECV) and histological ECV show a strong correlation. • T1 mapping with ECV measurement may be helpful for the noninvasive assessment of cRCC pathology, being a safe and feasible method, and it has potential to optimize individualized treatment options, e.g., in the decision of active surveillance.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Extracellular matrix; Extracellular space; Magnetic resonance imaging; Neoplasm grading; Renal cell carcinoma